EFEKTIVITAS MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING (CPS) DENGAN PENDEKATAN LEARNING COMUNITY TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIS: Array - Aristiyo, Dedi Nur; Muzayanti, Yulita (Universitas Peradaban, 2019)
This research aims to determine the average mathematical creative thinking ability of students using the CPS learning model with a complete learning comunity approach both individually and classically, the average mathematical creative thinking ability of the class given the application of the CPS learning model with a learning comunity approach is better than in the class using the expository model, there is a positive influence from the CPS learning model with the learning comunity approach to mathematical creative thinking abilities. The population in this research were all eighth grade students of Ma'arif NU Paguyangan Middle School 2015/2016 academic year. Sampling in this research was conducted by providing equal opportunities for each member of the population to be chosen as sample members (probability sampling), selected class VIII C as the experimental class using the CPS learning model with a learning comunity approach and class VIII D as a control class with expository learning . Data obtained by test, observation and documentation methods. Data analysis with individual completeness test, proportion test, average difference test and simple regression analysis. The results showed that the average mathematical creative thinking ability of students in the KKM complete experimental class was 78.03 and better than the mathematical class ability of creative thinking in the control class of 74.09, and there was an effect of 84.8% on students' ability mathematical creative thinking. Based on the results of the research it can be concluded that the CPS learning model with the learning comunity approach is effective on the students' creative mathematical thinking skills.